Tafsir Ayat-Ayat Al Qur’an Tentang Manajemen Konflik - Salman Alfarisi, Uswatun Hasanah Unsu Atikah Ahraini Nasution (Pusdikra Publishing, 2021)
Conflict is something that cannot be avoided in human life. Even as long as human life struggles with conflicts as well as in the life of an organization, members of the organization are faced with conflicts, changes or new innovations are very vulnerable to causing conflict (destructive) especially not accompanied by knowledge and understanding of religion, humans have special abilities and occupy the highest position among creatures. other. In the Al-Qur'an, much is described about the nature of conflict; conflict processes, sources of conflict and conflict resolution. The concept of conflict used in Management Science is basically the work of sociologists. Based on sociological research that studies human interaction, Management Science applies it to organizational management. Management practitioners realize that conflict is a conflict of interest caused by many factors within the organization. If conflict in the organization is not managed properly, it will have a negative impact on organizational performance. However, conflict management in the contemporary era is not to avoid conflict, because basically conflict is something that must exist in every community or organization. So managers are required to master the science and art of conflict management, so that conflict becomes functional for the organization.